Endophytic and antagonistic Bacillus amyloliquefaciens 8SE-IF1-derived nanoparticles encumber phytopathogenic oomycetes, fungi, bacteria, and viruses with enhanced growth in tomato seedlings - Sharmila, A. Mary; Johnson, Joy Michal; Sam, Saru Sara; Chandran, Deepa R.; Ajay, B.; Heera, G.; Sarada, S.; Thomas, Usha C.; Alex, Swapna; Radhakrishanan, N. V. (Frontiers in Microbiology, 2025)
Green synthesis of nanoparticles (Gs-NPs) of antimicrobial compounds from endophytic and antagonistic microbes is a novel strategy for managing plant diseases caused by different pathogens. The present study aims to green synthesize the NPs of water-diffusible antimicrobial metabolites (WDM) from the antagonistic and endophytic bacterial strain Bacillus amyloliquefaciens 8SE-IF1 (Ba-8SE-IF1) against phytopathogenic oomycetes, fungi, bacteria, and viruses infecting tomato plants. The water-diffusible extract (WDE) of Ba-8SE-IF1 significantly inhibited the mycelial growth of Pythium aphanidermatum (44.6%), Phytophthora nicotianae (60.1%), Fusarium oxysporum f. sp. lycopersici (65.5%), and Colletotrichum gloeosporioides (66.7%) in poisoned food assays; the growth of Ralstonia solanacearum and Xanthomonas campestris in the agar well method (inhibition zones of 20.25 mm and 28.52 mm, respectively); and decreased the symptoms produced by tomato spotted wilt virus (TSWV) in local lesion host (68.3%) and tomato leaf curl New Delhi virus (ToLCNDV) in tomato plants (66.1%). Gas Chromatography-Mass Spectrometry-Mass Spectrometry (GC-MS/MS) analysis of the WDE of Ba-8SE-IF1 identified 26 major organic compounds with antimicrobial properties. Five compounds, viz. phenol 3,5-bis (1,1-dimethyl-ethyl), hexadecane, 1-tetradecene, 2,6,10,14-tetramethyl hexadecane, and 2,6,11,15-tetramethyl hexadecane, exhibited simultaneous antioomycete, antifungal, antibacterial, and antiviral activities. The identified antimicrobial compounds were phenols, carboxylic acids, alcohols, carbonyls of aldehydes, and aliphatic hydrocarbons. The stable, crystalline, and functional zinc oxide nanoparticles of Ba-8SE-IF1-water diffusible metabolites with a size of approximately 60 nm were green synthesized (Gs-ZnO-NPs-Ba-8SE-IF1-WDM). Gs-NPs, even at 100 ppm, drastically reduced the growth of P. aphanidermatum (43.1%), P. nicotianae (62.7%), F. oxysporum f. sp. lycopersici (84.6%), C. gloeosporioides (81.7%), R. solanacearum (21.24 mm), and X. campestris (18.92 mm); and the symptoms produced by TSWV (69.9%) and ToLCNDV (62.6%). Gs-NPs at 100 ppm significantly reduced the incidence of bacterial wilt caused by R. solanacearum to < 10% compared to more than 60% in control plants. Additionally, Gs-NPs considerably promoted plant height, number of branches and leaves, leaf area, and shoot and root biomass. To the best of our knowledge, this is the first study demonstrating the potential of Ba-8SE-IF1 and its WDE and Gs-ZnO-NPs-WDM for the simultaneous control of phytopathogenic oomycetes, fungal, bacterial, and viral diseases with enhanced growth traits in tomato plants.